Field notes contributed by Russell P. Baldner, spring 1982 - Baldner, Russell P.et al (1982)
Field notes were contributed by Russell P. Baldner and other observers. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1982. Epson - sheet feed